Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am helping out a friend who can't seem to get these proofs and he enlisted my help thinking I know this. Unfortunately, I have tried wrapping my head around it and I can't find a solution to these problems.

Can someone tell me how to solve this or point me in the right direction with resources? Thanks!

Question 1:

 Prove that for all real numbers x, y, and z, if x + y + z greater than or equal 
 to 3, then either x greater than or equal to 1 or y greater than or equal to 1 
 or z greater than or equal to 1. 

$$\forall x,y,z\in \mathbb R, \quad x+y+z \geq 3 \implies x \geq 1 \lor y \geq 1 \lor z\geq1 $$

Question 2:

Prove that for all real numbers x and y, if xy less than or equal to 2, then 
either x less than or equal to square root of 2 or y less than or equal to 
square root of 2.  

$$\forall x,y \in \mathbb R,\quad xy \leq 2 \implies x \leq \sqrt 2 \lor y \leq \sqrt 2$$

share|improve this question

4 Answers 4

up vote 5 down vote accepted

Here are three ways you can choose to prove conditionals (if-then statements). There are other ways but these are most common.

Direct Proof

If $A$, then $B$.

$(A \implies B)$

Assume $A$ is true, then show that when $A$ is true that $B$ must also be true. This seems like it should be the simplest way, but that is not always the case.

Contrapositive

If not $B$, then not $A$.

$(\neg B \implies \neg A)$

This is when you assume that $B$ is false, then show that when $B$ is false then $A$ must also be false. This works because $(\neg B \implies \neg A)$ is logically equivalent to $(A \implies B)$.

Contradiction

$A$ and not $B$.

$(A \land \neg B)$

This is when you assume that $A$ is true and that $B$ is false. Then go on with attempting to prove that assumption just to arrive at a contradiction, or an absurdity in the proof. By showing $(A \land \neg B)$ is a contradiction you have done enough to prove that $(A \implies B)$ so you can end your proof there.

I know this is all formal symbolic logic but it's quite useful in math proofs. Hope that helps.

share|improve this answer

Proof 1.

By contradiction, x<1 and y<1 and z<1 implies x+y+z <3, so this assumption is false. Thus we have x>=1 or y>=1 or z>=1.

Proof 2 can be done in a similar way.

share|improve this answer
    
Thanks @ZhiyongWang. I'll try to do #2 and post my response here. –  AAA Mar 3 '13 at 0:53
    
I have a feeling I have it wrong but here it is: IF X <2 and y <2 then that implies that xy greater than or equal to 2. Thus we have xy greater than or equal to 2? –  AAA Mar 3 '13 at 1:07
    
@AAA That's not right. If $x<2$ and $y<2$ how do you get $xy\ge 2$? I edited my answer with a possible reasoning you can use, which is the one both me and Zhiyong have in mind. –  Git Gud Mar 3 '13 at 1:18

$$(A\Rightarrow B) \equiv (\lnot B\Rightarrow\lnot A)$$

  1. The statement is equivalent to its contraposition: if $x< 1$ and $y< 1$ and $z< 1$ then $x+y+z< 3$.
  2. Similarly, use contraposition.
share|improve this answer
    
Thanks @Berci. I'll try to do #2 and post my response here. –  AAA Mar 3 '13 at 0:55
    
@GitGud: yes, absolutely right. Was too late.. –  Berci Mar 3 '13 at 10:48
    
@Berci Comment deleted. –  Git Gud Mar 3 '13 at 15:34

Proof of part 1: Let $M$ be the largest value of $x,y,z$ then at most there are 3 different values : $M,M-a,M-b$ where $a,b \geq 0$.

Now writing $x+y+z \geq 3$ in terms of $M$ we have $$M+(M-a)+(M-b) \geq 3$$

$$3M-a-b \geq 3$$ $$3M \geq 3 +a + b$$ $$M \geq 1 + \frac {a}{3} + \frac{b}{3} \implies M \geq 1 $$ Since $a,b \geq 0 \implies \frac {a}{3} + \frac{b}{3}\geq0$ Since M was the maximum of $x,y,z$ then at least one of them $\geq 1 $ $$\square1$$

Proof of part 2: For part 2 we have : Let $M$ be the lowest value of $x,y$ then at most there are 2 different values $M,M\alpha$ where $\alpha \geq 1$

Now writing $xy \leq 2$ in terms of $M$ we have $$M(M\alpha)\leq 2$$
$$M^2\alpha\leq 2$$
$$M\leq \sqrt \frac{2}{\alpha}$$
But since $\alpha \geq 1 \implies \frac{2}{\alpha} \leq 2$ we have $$M \leq \sqrt \frac{2}{\alpha}\leq \sqrt 2$$
or just $$M \leq \sqrt 2 $$ $$\square 2$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.